STUDI TENTANG POLA HIDUP TIDAK SEHAT DALAM RANGKA PENINGKATAN TARAF KESEHATAN MASYARAKAT DI DESA KARANGGINTUNG KECAMATAN SUMBANG KABUPATEN BANYUMAS TAHUN 2009 - A. Haris Budi Widodo; Kusnandar Kusnandar (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2010)
ABSTRACT Government continue to try to improve level health of society through various developed program. Behavior of society represent one of the level determinant health of society. This Research aim to know various indisposed behavior which done by Countryside society of Karanggintung District Sumbang of Sub-Province of Banyumas. This type research is research of observasional with method survey and this research have the character of analytic descriptive, that is research elaborating and diging how a phenomenon happened. Population at this research is all citizen residing in or residing in Countryside of Karanggintung District Sumbang of Sub-Province of Banyumas counted 1.080 family head occupying house counted 973. Because research location do not too wide of, hence all population made as research sampel. Thereby this research is research of population. Data collecting done by observation or perception at research location. From result of research concluded as indisposed behavior which still done by Countryside society of Karanggintung District Sumbang of Sub-Province of Banyumas, covering: (1) take a bath, cleaning clothes and clean appliances/ housewares of household in river, (2) defecating, throwing away garbage and throw away family waste to river, (3) still many under the way house and look after livestock close to house, even include livestock into house, and (4) still many lawn or location which do not maintained (to be growed by crop no advantage, bamboo trees, big trees don't maintained, etc.), less grave location maintained, dirty gangways and growed by many grass, and also dirty street shoulders because grass and garbage) Keyword: Indisposed life pattern, Public health. Kesmasindo Volume 3, Nomor 1, Januari 2010, hlm. 66-75